The Pattern of Artistic Nationalism: Mexico's Pavilion at the Venice Biennale in the 1950s - Amelia Chávez Santiago (OBOE)
Mexico’s Pavilion at the Venice Biennale first exhibited in 1950, followed by another in 1952 and a final iteration in 1958. These three national pavilions showcased the canon of modern Mexican art, emphasising Figuration and Realism through painting and engraving. These artistic trends were strongly supported and promoted by the Mexican government, which sought to officially represent the nation through the most prominent artists of the Post-revolutionary Artistic Movement.